Fenomena Work life Boundary Management: Perjuangan Mengatur Batasan Kerja dalam Kehidupan Pribadi - Putri, Tiara Maharani; Syafira, Firnanda Inka; Sijabat, Rauly (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study analyzes the phenomenon of Work-Life Boundary Management: The Struggle to Manage Work Boundaries in Personal Life. The researchers used the qualitative data analysis model proposed by Miles, Huberman, and Saldana (2014), which includes three main components: data reduction, data display, and conclusion drawing and verification. The results indicate that the implementation of a hybrid work system provides employees with convenience in determining their work time and place. This flexibility allows employees to adapt work activities to their personal circumstances and the surrounding environment. However, work curiosity does not always have a direct positive impact, as in practice, employees still face difficulties in separating work time from personal time, especially when working from home.The research findings also reveal that the boundaries between work and personal life tend to be blurred. Employees often think about work outside of work hours without direct demands from the company. This situation indicates that work-life balance challenges stem not only from organizational policies but also from employees' own mindsets and work habits.